The effect of a 12-week combinational exercise program on CD4 count and mental health among HIV infected women: A randomized control trial - Mostafa Dianatinasab; Mohammad Fararouei; Valiollah Padehban; Aria Dianatinasab; Yousef Alimohamadi; Shohreh Beheshti; Zeinab AminiLari; Mahmood AminiLari (Journal of Exercise Science & Fitness, 2018)
Background/objective: There are conflicting results regarding the effects of exercise on immune function of HIV positive patients. Exercise can also be beneficial to psychological functioning of the patients. The purpose of this study was to determine the impact of a 12-week aerobic and resistance exercise training program on mental health and CD4 counts among female HIV+ patients. Methods: This clinical trial was conducted between September and December 2013. Forty participants (women age range 20–40) were carefully selected from 240 HIV-positive women referred to Voluntary Counseling and Treatment Center (VCT) and randomly assigned to either exercise (80 min of aerobic and strength training while receiving the VCT's routine services) group (n = 20) or control (received the VCT's routine services only) group (n = 20). To assess their mental health status, all participants completed GHQ28 questionnaire. Blood samples were collected to measure CD4 and T-cell counts at baseline and at the end of the 12-week intervention. Results: From a sample of 40 women with HIV infection, the data of 30 participants [experimental group (14) and control group (16)] were analyzed (participation rate 75%). The results indicated that after the intervention program, a significant difference in CD4 cell counts was found between the two groups (P = 0.01). With regard to mental health, after performing intervention, significant improvement in all subscales including anxiety disorder, social function, depression and mental health's total score was observed in the exercise compared to the control groups (P < 0.001). Conclusion: Exercise training can be included in health care services in order to improve the mental health status of women with HIV infection. No effect on CD4 count was detected. Keywords: Exercises training, Mental health, CD4 count, HIV infected women